Esophagopleural fistula treated with muscular ventricular septal defect occluder - Rafael Vera-Urquiza (Permanyer, 2021)
To the Editor, Esophageal-pleural fistulas are a rare complication of thoracic surgery. They may occur as the direct result of trauma during surgery or use of a transesophageal device. The management of esophageal-pleural fistulas can be difficult, and they rarely heal spontaneously. Conservative management of esophageal-pleural fistulas are associated with high mortality rates. The traditional treatment of symptomatic patients is surgery. However, this type of surgery has high morbidity and mortality rates; for this reason, many patients are not eligible for surgery. The endoscopic treatment options to repair esophageal fistulas include the injection of glue, covered stents, and endoscopic suture or clipping. After treatment failure, we considered the use of an emerging therapeutic technique as an alternative treatment. In this context, we present a case of a iatrogenic esophageal fistula treated with an Amplazer device. This is the case of a 72-year-old woman, former smoker with a past medical history of hypertension, chronic atrial fibrillation, and rheumatic mixed mitral valve disease who was admitted due to acute coronary syndrome. A thrombotic occlusion...